Weed Control in Eggplant: HS191/WG030, rev. 4/2009 - Stall, William M. (EDIS, 2009)
Revised! HS-191, a 3-page fact sheet by William M. Stall, describes effective weed management practices for cultivation of eggplant in Florida, and a table of chemical weed controls. Published by the UF Department of Horticultural Sciences, April 2009. HS191/WG030: Weed Management in Eggplant (ufl.edu)